The Fresh Fruit Bunch Boiling Process at the Sterlizer Station in Palm Oil Processing at PT. Sumber Bumi Sawit Jadi Jaya - Yabes Cristian Nainggolan; Tambos August Sianturi (Journal Of Global Research Publications, 2026)
This study aims to analyze the Fresh Fruit Bunch Boiling Process at the Sterlizer Station in Palm Oil Processing at PT. Sumber Bumi Sawit Jadi Jaya. In writing this report, data collection is very important. The data collection methods used by the author are as follows: Documents or References Data collection through written and electronic documents from PT. Sumber Bumi Sawit Jadi Jaya. Field Observation. The method is carried out by direct observation in the company environment. Literature Review. In addition to field observations, data is also taken from several literatures related to this report. The location of the field work practice was held at PT Sumber Bumi Sawit Jadi Jaya which is located on Jalan Besar Mandoge-Kisaran. And the field work practice lasted for 1 month. Starting from September 1st – October 1st, 2023. The conclusions obtained from the results of the practical work are as follows: PT. Sumber Bumi Sawit Jadi Jaya is a factory that processes fresh oil palm fruit bunches into CPO and palm kernel. The processing capacity at PT. Sumber Bumi Sawit Jadi Jaya is 30 Tons of FFB / Hour The organizational structure at PT. Sumber Bumi Sawit Jadi Jaya is a functional organizational structure. The results of processing the percentage of cardiovascular load obtained that all boiler workers needed repairs, and the workload category of the four workers was influenced by age factors